The Effect of Detethering Surgery on the Bladder Function and Psychology of Children with Primary Tethered Cord Syndrome - Shuai Yang; Zhaokai Zhou; Xingchen Liu; Zhan Wang; Yanping Zhang; He Zhang; Lei Lv; Yibo Wen; Qingwei Wang; Wei Jia; Jinhua Hu; Jian Guo Wen (International Brazilian Journal of Urology)
ABSTRACT Purpose: Currently, detethering surgery (DS) is the modality most extensively utilized to treat primary tethered cord syndrome (TCS). Disappointingly, some children without bladder impairment showed a deterioration of bladder function after surgery, which critically influences the health-related quality of life. It was hypothesized that the DS might have a significant effect on bladder function and psychology. Therefore, the purpose of this study was to investigate the effect of DS on bladder function and quality of life in children with primary TCS. Materials and Methods: A retrospective study of 83 patients aged 6 to 10 years who were diagnosed with TCS and underwent DS between 2022 and 2023. The urodynamic parameters and score, psychological-behavioral profile, and lower urinary tract symptoms were compared before and after DS. Additionally, the patients were divided into the normal group and the abnormal group according to the preoperative urodynamics parameters. Results: A total of 66 children fulfilled the criteria, with a mean age at surgery of 89.5 ± 13.7 months. There were statistically significant differences in bladder detrusor sphincter synergy and urodynamic score and no statistically significant difference in the remaining urodynamic parameters and psychological-behavioral items before and after DS. The proportion of bladder dysfunction that improved or did not worsen after surgery was higher in the Abnormal group than in the Normal group. Nevertheless, the detection rate of each psychological behavior abnormality in children with TCS was higher compared with that of normal children, both preoperatively and postoperatively. Conclusions: DS could not considerably ameliorate pre-existing bladder dysfunction and patients exhibiting non-progressive bladder dysfunction could be treated conservatively with close observation. TCS plagues patients all the time even if detethering. Psychological counseling for children with TCS should be strengthened after DS.